How does mindful awareness impact academic performance in junior high school students? A chain mediation effect based on academic self-efficacy and academic buoyancy - Guo, Jianwen; Zhang, Jiahao; Qiao, Lei; Zhou, Yun (Frontiers in Psychology, 2025)
BackgroundPrevious research has mostly focused on exploring the mechanisms of mindful awareness and academic performance in university students, with less attention paid to junior high school student group. This study aimed to examine how mindful awareness influences academic performance in junior high school students through the chain mediation of academic self-efficacy and buoyancy.MethodsThe study selected 3,163 Chinese junior high school students (1,599 males, 1,564 females; mean age = 13.30, standard deviation = 0.90), and assessed their mindful awareness, academic buoyancy, academic self-efficacy, and academic performance through a survey.ResultsThe results showed that mindful awareness had a significant positive effect on academic performance (β = 0.179). This relationship was partially mediated through two pathways: academic self-efficacy (β = 0.083) and academic buoyancy (β = 0.035). Additionally, a serial mediation pathway through both mediators was significant (β = 0.024). These indirect effects collectively accounted for 44.2% of the total effect, suggesting that mindful awareness enhances academic performance both directly and indirectly through increased academic self-efficacy and buoyancy.ConclusionThe research findings provide a theoretical and practical basis for enhancing students’ positive psychology and promoting academic performance through mindful awareness interventions. These findings suggest that schools could improve student outcomes by integrating mindfulness practices (e.g., brief pre-class meditation) into support programs.